2018
DOI: 10.1007/s11060-018-2854-0
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human intraoperative near-infrared fluorescence imaging of glioblastoma using cetuximab-IRDye800

Abstract: Introduction Maximizing extent of surgical resection with the least morbidity remains critical for survival in glioblastoma patients, and we hypothesize that it can be improved by enhancements in intraoperative tumor detection. In a clinical study, we determined if therapeutic antibodies could be repurposed for intraoperative imaging during resection. Methods Fluorescently labeled cetuximab-IRDye800 was systemically administered to three patients 2 days prior to surgery. Near-infrared fluorescence imaging of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 22 publications
1
120
1
1
Order By: Relevance
“…Targeted NIR fluorescence imaging has already been studied in several clinical trials for colorectal, head and neck, pancreatic and renal cancer and has shown its potential and added value in intraoperative decision making 21,25,[31][32][33] . As a result of these trials, a variety of suitable biomarkers have been identified for NIR-fluorescence guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted NIR fluorescence imaging has already been studied in several clinical trials for colorectal, head and neck, pancreatic and renal cancer and has shown its potential and added value in intraoperative decision making 21,25,[31][32][33] . As a result of these trials, a variety of suitable biomarkers have been identified for NIR-fluorescence guided surgery.…”
Section: Discussionmentioning
confidence: 99%
“…défini par l'agence européenne des médicaments (EMA, European medicines agency) et la FDA (food and drug administration), n'a pas permis l'évaluation peropératoire des marges chirurgicales [25]. Sept études ont évalué le cétuximab (anti-EGFR)-IRDye800CW essentiellement dans les cancers otorhino-laryngés (ORL) (37 patients au total [26][27][28][29]) et les adénocarcinomes pancréatiques (14 patients au total [30,31]), puis dans une étude pilote de 3 patients pour le glioblastome [32]. Une fluorescence spécifique a été observée dans une majorité des cas avec des doses injectées relativement élevées en raison de l'expression de l'EGFR dans les tissus normaux.…”
Section: Revuesunclassified
“…This concept was initially approached by conjugating conventional passive dyes, such as fluorescein [24] and ICG [25], to targeting molecules but then the interest shifted towards more suitable fluorescent dyes which need be well tolerated, able to produce high-contrast image, and suitable for bioconjugation [22,26,27]. One of the dyes that fulfills these criteria and has shown the most promising results in clinical trials is IRDye800CW (IR800) [11,28]. This dye has an excellent safety profile and can be visualized by existing equipment developed for widespread FDA-approved dye indocyanine green, and its conjugates with anti-EGFR antibodies have been successfully used in preclinical and clinical trials for GBM and other cancers [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%